Explorative methods for turbulent flow control - Basso, Alessio (2018)
Turbulent skin-friction is a matter of importance for the aerospace sector, where the increase in fuel costs is of concern. In view of this consideration, the aircraft aerodynamic efficiency can be increased by reducing turbulent drag. In fact, turbulent drag can up to 45% of the total drag force encountered in subsonic commercial transportation. Four different concepts have been relevant over the last few decades to achieve turbulent skin-friction reduction: - Fluid suction; - Tangential gas injections; - Particle additives applied to main flow stream; - Compliant walls.